The Meaning Of Divorce For Wives (The Marriage Age 20 Years And Above) - Eva Meizara Puspita Dewi (Program Studi bimbingan Konseling PPs UNM Makassar, 2017)
This study aims to (1) describe the overview of the life of the Marriage (2) Explain the reason for the wives did divorce at the age of marriage has reached 20 years (3) Knowing the psychological condition of the subjects post-divorce. This study uses a qualitative method of data collection in the form of interviews and documentation. The research subjects are four and add with the informant as much as four people. The results of this research are (1) Household life subjects had massive conflicts, domestic violence and even infidelity. The conflict that often occurs and the lack of ability to make problem solving the complex problems faced. Child's attitude does not affect the subject's decision to divorce. (2) A lot of unpleasant incident in the relationship of husband and wife for households. Subjects have been feeling tired and physically to survive, while there was no sign of positive change of her husband, the kids are great, economically ex-husband and the family is quite helpful and the subjects feel life itself will be better then the subject decided to divorce. Perception wife, honored to perform contested normal divorced from the talak divorce. (3) Subject to feel more calm because of the conflict intensity dropped dramatically after the divorce for no longer live at home with her husband. Subjects had a lot of time to themselves and deepen the use of religion and worship. Only in this way, the subject may continue to be grateful and do not regret the past life. However, the subjects had to make a living despite the additional subsidy granted by the former husband. In the social interaction is often the subject of conversation to be sensitive to neighbors or group those talks about divorce.